2013
DOI: 10.4103/2321-3868.113329
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm delays wound healing: A review of the evidence

Abstract: Biofilm is the predominant mode of life for bacteria and today it is implicated in numerous human diseases. A growing body of scientific and clinical evidence now exists regarding the presence of biofilm in wounds. This review summarizes the clinical experiences and in vivo evidence that implicate biofilm in delayed wound healing. The various mechanisms by which biofilm may impede healing are highlighted, including impaired epithelialization and granulation tissue formation, and reduced susceptibilities to ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
154
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(162 citation statements)
references
References 55 publications
1
154
1
6
Order By: Relevance
“…Both enzymatic and mechanical debridement play a role in this pathway, with mechanical debridement especially important in the presence of biofilms. [41][42][43] Moisture balance is the assessment and management of wound exudate, of which mismanagement results in either desiccation, which slows epithelial cell migration, or excessive fluid, which causes maceration of wound margins. 27,28,[37][38][39] Finally, Edge of wound assesses the non-advancing or undermined wound edges.…”
Section: Introductionmentioning
confidence: 99%
“…Both enzymatic and mechanical debridement play a role in this pathway, with mechanical debridement especially important in the presence of biofilms. [41][42][43] Moisture balance is the assessment and management of wound exudate, of which mismanagement results in either desiccation, which slows epithelial cell migration, or excessive fluid, which causes maceration of wound margins. 27,28,[37][38][39] Finally, Edge of wound assesses the non-advancing or undermined wound edges.…”
Section: Introductionmentioning
confidence: 99%
“…Bakterie tworzące biofilm wydzielają do macierzy biopolimery białkowo-cukrowe chroniące je przed atakiem ze strony układu odpornościowego oraz stosowanymi antybiotykami [10][11][12]. Biofilm jest złożony z wielu ściśle współpracujących gatunków bakterii, które współdziałają podobnie jak organizm wielokomór-kowy [13].…”
Section: Wpływ Biofilmu Bakteryjnego Na Gojenie Ran Przewlekłychunclassified
“…Translational research [4][5][6] has shown that when biofilm is deliberately introduced into controlled wound models in vivo, infection may ensue, healing is delayed, and interventions to remove wound biofilm reverse this delay. 7 In subjects with comorbidities, wound healing has been observed to be delayed more so than in wild-type subjects, [8][9][10] suggesting interactions between host factors and microbial bioburden.…”
Section: Translational Relevancementioning
confidence: 99%